Pengaruh Pembelajaran Kooperatif Tipe Group Investigation (GI) Terhadap Kemampuan Pemecahan Masalah Matematis Dan Percaya Diri Siswa SMP Negeri 2 Rembang - Khotijah Priyatin (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
This study aims to determine the effect of Group Investigation type cooperative learning on mathematical problem solving abilities and confidence of class VII students of Rembang 2 State Junior High School 2017/2018 school year. The population in this study were seventh grade students of Rembang 2 State Junior High School 2017/2018 school year. The sample in this study is class VII E as the Experiment class and VII C as the Control class which is taken by Cluster Random Sampling technique. The instrument used in this study is post test. Post test results were obtained after students in the experimental class followed Group Investigation cooperative learning and the control class followed direct learning. Post test results were processed using IBM SPSS Statistic 21 Software by performing the Mann Whitney test for post test results and Independent t Test tests on questionnaire results. The sig value obtained on the Mann Whitney test for post test results is 0.0355 and the sig value on the Independent t-test for the results of the questionnaire is 0.0075. So it can be concluded that students' mathematical problem solving and self-confidence abilities that follow Group Investigation type cooperative learning are better than mathematical problem solving abilities and confidence by using direct learning.